Environmental Effectiveness Assessment of the Fast Fashion Industry - Ma, Guangping; Martínez, Felipe; Kupec, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This study aims to explore whether the actions of fast fashion companies have reduced their impact on the environment and how to truly achieve sustainable development.Using the ISO 14001 environmental management standard, sustainable development goals and FMEA tools, key environmental risks in the supply chain were identified, and public reports of fast fashion companies were analyzed to determine whether their actions were consistent with actual operations.The analysis showed that despite some progress, serious problems still exist in areas such as supply chain transparency, wastewater treatment and carbon emissions, and many high-polluting suppliers are still not properly regulated.The results show that the environmental strategies of the fast fashion industry are often superficial and lack practical actions. Based on the data and existing information, this paper proposes suggestions for improvement.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses